2003
DOI: 10.1002/anie.200390306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Redox‐Active Dodecamethoxoheptaoxohexavanadium Clusters

Abstract: The chemical behavior of alkoxo-oxovanadium clusters lies between that of metal oxides and metal alkoxides. [1,2] These compounds are important as precursors for the synthesis of new polyoxometalates and as reagents for sol-gel processes and chemical vapor deposition (CVD) methods for the generation of metal oxides.[3] The interest in this substance class for basic research as well as for technical applications is attributed to vanadium's facile and often reversible change in its oxidation state.[4] By varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 21 publications
(11 reference statements)
5
137
0
Order By: Relevance
“…12 compound belongs to the P 2 1 /n space group with four magnetically non-equivalent cluster-molecules in the unit cell [10,11]. In each mixed valent cluster V vanadium nuclei all equally bind one terminal oxygen atom and four µ 2 -bridging methoxo ligands, respectively (see Table and • .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 compound belongs to the P 2 1 /n space group with four magnetically non-equivalent cluster-molecules in the unit cell [10,11]. In each mixed valent cluster V vanadium nuclei all equally bind one terminal oxygen atom and four µ 2 -bridging methoxo ligands, respectively (see Table and • .…”
Section: Resultsmentioning
confidence: 99%
“…We shall begin the discussion of the V Table) and corresponds to the valence-sum calculations [11]. The spin Hamiltonian can thus be written as…”
Section: An Individual Vmentioning
confidence: 99%
“…This serves to diminish the charge, and a reducing state of V IV is preferred by the introduction of alkoxide ligands [83]. The substitution of all bridging oxygens with CH 3 O - [84,85] [98]. This straightforward synthesis of alkoxides provides a facile route for further development of polyoxovandate synthesis.…”
Section: Alkoxohexavanadatesmentioning
confidence: 99%
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) Hartl et al [6,7] In these complexes, the hexavanadate core contains an OV 6 unit in which the vanadium ions are arranged in an octahedral fashion; six oxo groups act as terminal ligands and twelve alkoxo groups act as bridging ligands. The chemical synthesis and crystal structures of such alkoxo-polyoxovanadium compounds differing in their V IV content (n = 2, 3, 4, 5, 6) have been described (see Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] It has been found that unstable POM architectures can be stabilized by the introduction of alkoxo ligands because of the charge compensation associated with formal substitution of peripheral oxo ligands. [5] Among many other alkoxo-polyoxometalates, the fully alkylated polyoxovanadate derivatives [V IV n V V 6-n O 7 (OR) 12 ] (4-n) (R = CH 3 , C 2 H 5 ) of the classical (Lindqvist) POM structure [M 6 O 19 ] n-, which as an entity is not known for vanadium, have been reported by Such interactions are very rare in oxovanadium complexes and are a consequence of a specific core geometry imposed by the polyoxometalate architecture. It has been shown that the earlier proposed intramolecular electron transfer cannot change the ground spin-state multiplicity irrespective of the sign of the exchange parameters.…”
Section: Introductionmentioning
confidence: 99%